Increased expression of collagenase-3 (MMP-13) and MT1-MMP in oesophageal cancer is related to cancer aggressiveness. Issue 1 (1st July 2000) - Etoh, T; Inoue, H; Yoshikawa, Y; Barnard, G F; Kitano, S; Mori, M
Abstract : BACKGROUND: Collagenase-3 (matrix metalloproteinase-13, MMP-13) is a recently identified human MMP with broad substrate specificity which can be activated by membrane type 1 (MT1) matrix metalloproteinase in vitro. These may play a critical role in cancer aggressiveness. AIMS: To examine the clinical significance of collagenase-3 expression and the cooperative role of MT1-MMP in human oesophageal carcinomas. PATIENTS: Forty five individuals with oesophageal carcinoma who underwent surgery without preoperative treatment. METHODS: The tumour/normal (T/N) ratios of collagenase-3 and MT1-MMP mRNA expression in 45 human oesophageal carcinomas were determined by northern blot analysis. The production and localisation of collagenase-3 and MT1-MMP proteins were investigated by immunohistochemistry, western blot analysis, and zymography. RESULTS: The mean T/N ratio of collagenase-3 mRNA was 3.5 and that of MT1-MMP 2.1. There was a significant correlation between collagenase-3 and MT1-MMP mRNA expression (p<0.001). Twenty two cases with a collagenase-3 T/N ratio >3.5 showed a significantly higher frequency of vascular involvement and lymph node metastasis, and tended to be at a more advanced stage than 23 cases with a T/N ratio ⩽3.5 (p<0.05). Western blot analysis and zymography demonstrated production of collagenase-3 protein in tumour tissues but not in normal tissues. Immunohistochemical studies revealed that collagenase-3 was localised predominantly in tumour cells and MT1-MMP was detected in the same collagenase-3 positive cells; there was a significant association between collagenase-3 and MT1-MMP protein expression (p<0.05). With regard to prognosis, the survival time for subjects in the high collagenase-3 group (T/N ratio >3.5) was significantly worse (p<0.05) . CONCLUSIONS: These data suggest that production of collagenase-3 together with MT1-MMP is implicated in tumour aggressiveness and prognosis in human oesophageal carcinomas.